Development of a STEM-Based E-Module Integrated with Environmental Projects to Stimulate Senior High School Students’ Critical and Creative Thinking Skills - Metia Vinliani; Jayanti Syahfitri; Kashardi Kashardi (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
This study aimed to develop a Science, Technology, Engineering, and Mathematics (STEM)-based e-module integrated with environmental projects on environmental pollution topics to stimulate senior high school students’ critical and creative thinking skills, as well as to examine its validity and practicality. The study was motivated by the limited availability of digital learning materials integrating real environmental contexts, STEM activities, and project-based learning in Biology instruction. The research employed a Research and Development method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants involved 104 public senior high school students in Bengkulu City, including 36 students in the limited trial and 68 students in the large-scale trial. Data were collected through content expert validation sheets, media expert validation sheets, student response questionnaires, and teacher response questionnaires, and analyzed using descriptive quantitative and qualitative techniques. The findings indicated that the developed e-module achieved a very high validity level, with content validation of 92% and media validation of 98%. The practicality test also showed that the e-module was categorized as very practical based on students’ and teachers’ responses. These findings demonstrate that the developed e-module is feasible for supporting contextual Biology learning and fostering students’ critical and creative thinking skills.